Empowering genomic medicine by establishing critical sequencing result data flows: the eMERGE example. (31st May 2018) - Aronson, Samuel; Babb, Lawrence; Ames, Darren; Gibbs, Richard A; Venner, Eric; Connelly, John J; Marsolo, Keith; Weng, Chunhua; Williams, Marc S; Hartzler, Andrea L; Liang, Wayne H; Ralston, James D; et al.
Abstract: The eMERGE Network is establishing methods for electronic transmittal of patient genetic test results from laboratories to healthcare providers across organizational boundaries. We surveyed the capabilities and needs of different network participants, established a common transfer format, and implemented transfer mechanisms based on this format. The interfaces we created are examples of the connectivity that must be instantiated before electronic genetic and genomic clinical decision support can be effectively built at the point of care. This work serves as a case example for both standards bodies and other organizations working to build the infrastructure required to provide better electronic clinical decision support for clinicians.